Análise de prontuários dos pacientes atendidos pelo curso de quiropraxia no período de 2003 a 2012 – experiência na Universidade Anhembi Morumbi - Benedicto, Camila de Carvalho (2015)
The present dissertation aims at apprehending and analyzing the view of students of the 8th grade on preventing drug use in school environments. For conducting its case study, this research, a qualitative one, has elected a school, located in the East side of São Paulo (SP), from the City Hall System. A bibliographical review, document analysis and field research were used as methodological procedures. Questionnaires with objective and open questions were applied. Afterwards, some interviews were made. The Pedagogical Project of the school was also analyzed, as well as the written records of the activities performed in the last two years, trying to identify the carried out actions, to verify how they were structured and whether they had any effect on the students’ formation. The results showed that in this school the events only occurred sporadically and they focused only students of the 4th grade. Students, teachers and directors consider it is necessary a program for preventing drug use. However, meanwhile the students pointed out the actions have to be conducted by, mainly, teachers, coordinators and directors, the latter indicated they should be conducted by specialists, external from schools. It is expected this research can contribute for a greater reflection about the accomplishment of such a program of prevention to be conducted with the participation of the subjects of the school in all its phases, since the planning, the execution, the evaluation and, again, the replanning. This possibility has been shown as viable from the motivation point of view because, during the research, the participants were very receptive and made a lot of suggestions on this direction.